Single‐Atom Iron‐Nitrogen Catalytic Site with Graphitic Nitrogen for Efficient Electroreduction of CO2. Issue 4 (24th January 2020) - Zhu, Ying; Li, Xueyan; Wang, Xingpu; Lv, Kuilin; Xiao, Guozheng; Feng, Jingjing; Jiang, Xiaohui; Fang, Mingwei; Zhu, Ying
Abstract: Electrochemical reduction of CO2 to carbon monoxide (CO) and other useful fuels/chemicals offers a green and promising technical solution for alleviating greenhouse effect and creating economic benefits. Herein, we developed a single‐atom Fe dispersed on N‐doped carbons nanosheet (Fe−SA/NCS−X) for CO2 electroreduction by direct pyrolysis of hemin‐doped polyaniline fabricated by in‐situ chemical polymerization. The Fe‐SA/NCS‐700 achieved a Faraday efficiency of CO up to 87 % at −0.45 V vs. RHE, a low onset overpotential of 105 mV and remarkable durability with the current density being maintained for 10 h constant electrocatalysis, which were comparable to the latest reported single‐atom catalysts. The Tafel slope of Fe‐SA/NCS‐700 was measured to be about 67 mV/dec, close to theoretical value of 59 mV/dec, which indicated a rapid pre‐equilibrating one‐electron transfer followed by a rate‐determining reaction step. DFT calculations revealed that the graphitic N species can synergistically improve the catalytic activities of Fe‐N4 sites of Fe‐SA/NCS−X by significantly lowering the free energy barriers of *COOH intermediate formation, thus promoting CO2 electroreduction to CO. Abstract : A single‐atom Fe dispersed on N‐doped carbons nanosheets (Fe−SA/NCS−X) with high activity and selectivity for CO2 electroreduction to CO was designed and developed by pyrolyzing precursor of hemin‐doped polyaniline.